Incidence and risk factors for major bleeding among patients undergoing percutaneous coronary intervention: findings from the Norwegian coronary stent trial (NORSTENT). (25th November 2020) - Samuelsen, P; Eggen, A.E; Steigen, T; Wilsgaard, T; Kristensen, A; Skogsholm, A; Holme, E; Van Den Heuvel, C; Nordrehaug, J.E; Bendz, B; Nilsen, D.W.T; Bonaa, K.H
Abstract: Introduction: Bleeding is a concern after percutaneous coronary intervention (PCI) and subsequent dual antiplatelet therapy (DAPT). Purpose: We herein report the incidence and risk factors for major bleeding in the Norwegian Coronary Stent Trial (NORSTENT). Materials and methods: NORSTENT was a randomized, double blind, pragmatic randomized trial among patients with acute coronary syndrome or stable coronary disease undergoing PCI during 2008–11. The patients (N=9, 013) were randomized to receive either a drug eluting stent or a bare metal stent, and were treated with at least 9 months of DAPT. The patients were followed for a median of five years, with BARC 3–5 major bleeding as one of the safety endpoints. We estimated cumulative incidence by a competing risks model and risk factors through cause-specific Cox models. Results: The 12-month cumulative incidence of major bleeding was 2.3%. Independent risk factors for major bleeding were chronic kidney disease (CKD), underweight (<60 kilograms), diabetes mellitus, and advanced age (>80 years). A myocardial infarction (MI) or PCI during follow-up increased the risk of major bleeding (HR = 1.7, 95% CI 1–3-2.2). Conclusions: The 12-month cumulative incidence of major bleeding in NORSTENT was higher than reported in previous, explanatory trials. This analysis strengthens the role of CKD, advanced age, and underweight as risk factors for major bleeding among patients receiving DAPT after PCI. The presence of diabetes mellitus or recurrent MI among patients is furthermore a signal of increased bleeding risk. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Northern Norway Regional Health Authority (Helse Nord RHF)